Xây dựng và thẩm định quy trình định lượng Pinoresinol Diglucosid trong cao khô đỗ trọng bằng phương pháp HPLC / Trần Thanh Tâm, Nguyễn Đức Hạnh, Huỳnh Trần Quốc Dũng, Nguyễn Đức Tuấn - Trần, Thanh Tâm
An HPLC for determination of the bioative phytochemical component named pinoresinol diglucoside (PDG) of Eucommia ulmoides Oliv., Eucommiaceae known as a biomarker for the plant spray-dried extracts. The procedure was optimized as: Column - Gemini NX C18 (250 x 4.6 mm; 5 μm), column temperature – 30 oC; Detector - UV (228 nm); Flow rate - 0.8 ml/min; Mobile phase - acetonitrile and water (in gradient mode, with acetonitrile (%) were 10, 18 %; 50 %; and 10 % at the corresponding time interval of 0-1.0; 1.0-17.0; 17.1-22 and 22.1-28 min. By validation, the proposed method proved the good compatibility, specificity and linearity (R2 = 0.9994). The RSD values of the intra-day and inter-day precision were 0.28 % and 0.48 %, respectively, and the recovery percentages 98.07 – 98.35 %. In short, the proposed method met the requirements of validation and could be useful for establishing the quality standard of the E. ulmoides spray-dried extract and its related products.